1977
DOI: 10.1111/j.1476-5381.1977.tb07523.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Cardiovascular Effects of Pindolol in Doca/Saline Hypertensive Rats

Abstract: 1 A hypotensive response to orally administered pindolol in conscious normotensive and deoxycorticosterone acetate (DOCA)/saline hypertensive rats (DS‐rats) is described. In DS‐rats, pindolol (10‐50 μg/kg) produced a dose‐dependent fall in blood pressure and elevation of resting heart rate. 2 The hypotensive response and tachycardia produced by oral pindolol (50 μg/kg) in DS‐rats were prevented by propranolol (5 mg/kg), suggesting that pindolol's effects are mediated by β‐adrenoceptor stimulation. 3 After meca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
1

Year Published

1978
1978
1985
1985

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
(24 reference statements)
0
6
1
Order By: Relevance
“…Introduction The non-selective fl-adrenoceptor blocking drug, pindolol, has been shown to lower the blood pressure of deoxycorticosterone acetate (DOCA)-saline hypertensive (DS) rats after oral administration of small doses (Buckingham, Hamilton & Robson, 1977). The effect was dose-related and appeared to be mediated by a metabolite(s) acting by stimulation of vascular fi2-adrenoceptors.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Introduction The non-selective fl-adrenoceptor blocking drug, pindolol, has been shown to lower the blood pressure of deoxycorticosterone acetate (DOCA)-saline hypertensive (DS) rats after oral administration of small doses (Buckingham, Hamilton & Robson, 1977). The effect was dose-related and appeared to be mediated by a metabolite(s) acting by stimulation of vascular fi2-adrenoceptors.…”
mentioning
confidence: 99%
“…Pindolol is extensively metabolized in rats (Kiechel, Niklaus, Schreier & Wagner, 1975) and has a short plasma half life after oral administration (Pacha, 1969). Our earlier studies (Buckingham et al, 1977) suggested that the hypotensive response to pindolol in the DS-rat is mediated through a metabolite(s) formed predominantly in the liver. Over-loading of the hepatic extraction process, by administration of a sufficiently large oral dose, would reduce the fraction of drug removed on its first passage through the liver, as occurs with propranolol in the rat (Shand, Rangno, & Evans, 1972).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although metabolites of pindolol have been found to be pharmacologically active in the rat (Buckingham et al, 1977), no evidence of active metabolites of pindolol in man has been forthcoming (Aellig, 1976b). Although similar oral and intravenous doses produce the same 0-adrenoceptor blockade (Carruthers, 1982), there has never been any comparison of the plasma concentration-response relationships of pindolol after oral and intravenous administration in the manner described for oral and intravenous propranolol by Cleaveland & Shand (1972).…”
Section: Introductionmentioning
confidence: 99%